Clinical profile of the first 1000 fatalities for influenza A (H1N1) in Mexico - Fajardo-Dolci, Germán; Gutiérrez-Vega, Rafael; Durán-Arenas, Luis; Hernández-Ramírez, Luz del Carmen; Garrido-Solano, Carlos; Franco-Marina, Jesús; García-Moreno, Juan; Valderrama-Treviño, Alan Isaac; Montalvo-Javé, Eduardo E. (International Journal of Research in Medical Sciences, 2017)
Background: Influenza is an acute respiratory disease responsible for several episodes of high mortality throughout human history. In 2009, Mexico experienced an atypical influenza outbreak caused by a mutant strain of the influenza A (H1N1) subtype, which generated significant mortality. The aim of this paper was to analyze the clinical and sociodemographic conditions of the first 1000 fatalities recorded during this outbreak. Methods: We conducted a study based on an analysis of the clinical files of patients positive for influenza A (H1N1) using Real-Time-Polymerase Chain Reaction (RT-PCR) to conduct an analysis of deaths compared to deaths in the general population. Results: The majority of deaths occurred in patients aged 35-84 years (65.8%). Average time between symptom onset and death was 13.8 days, with an average of 7.8 days from time of hospitalization until death. Ca. 25% of deaths occurred in residents from Mexico City and from the nearby State of Mexico. In the majority of cases, we found that patients who died had a low educational and socioeconomic status along with co-morbidities such as metabolic syndrome and its individual components, as well as respiratory illnesses. In 80% of cases, patients received mechanical ventilation, and a similar percentage received antiviral therapy (oseltamivir, zanamivir). Conclusions: The primary-care level was not utilized by patients who died from influenza. The higher prevalence of chronic degenerative diseases among deaths compared with the general population indicates that these groups of patients should be considered and prioritized in the event of future outbreaks.